Autonomic nervous system: training, detraining and retraining - Pagani, M.; Lucini, D.; Pizzinelli, P. (International Congress Mountain & Sport. Updating study and research from laboratory to field. 11th-12th November 2005. Rovereto (TN) - Italy. Programme and book of abstracts, 2005)
Introduction: The cardiovascular response to acute bouts of physical exercise is characterized by rapid and substantial increases in cardiorespiratory performance, as witnessed by increases in heart rate, myocardial contractility, cardiac output and systolic arterial pressure which are accompanied by a drastic rise in ventilation, and an attendant increase in oxygen consumption. VO2max is accordingly accepted as an overall measure of exercise capacity both in health and disease. Long term adaptations to exercise are as well documented by various molecular and functional changes, such as a consistent rise in VO2max or a clear resting bradycardia. In addition, it is well recognized that the autonomic nervous system contributes substantially to the short and long term adaptations to physical exercise both in animals and in humans. However, gauging the perception of the importance of various components of the exercise response by the percentage of papers that in the Medline database addressed simultaneously exercise and either anatomical (such as muscle) or functional components (e.g., oxygen consumption, or autonomic regulation) provides unexpected results. In fact, of the papers dealing in the last 10 years with physical exercise, about 30% addressed simultaneously with exercise either the indicated functional or anatomical components, but only about 0.5% addressed its combination with the Autonomic nervous system. This apparently reduced interest about autonomic regulation of exercise might well depend from various causes, among which the difficulty of assessing autonomic performance in the context of exercise could be of paramount relevance. Even more apparent is the limited knowledge about dynamical adaptation of the autonomic nervous system (in its vagal or sympathetic branches) when considering the effects of ipomobility (and other forms of reduced load, such as detraining, microgravity or aging) or related countermeasures, such as retraining. Methods and Results: In addition to ad hoc imaging, various available techniques to assess autonomic regulation, employing either measures derived from plasma catecholamines or physiological parameters, including direct assessment of sympathetic efferent muscle nerve activity (MSNA), are easily employed at rest, before or after exercise, but relatively few methods can provide an assessment of autonomic regulation during exercise. Of course this latter aspect plays a crucial role in a complete description of autonomic adaptation to physical exercise. Accordingly we will focus our attention on the specific applications of heart period and arterial pressure variability to assess autonomic changes induced by acute and chronic exercise. Some specific aspects, such as the possibility of assessing rapid and slow adaptations of sympatho-vagal balance only within a given experimental window will be addressed. In addition the somewhat analogous influence of mental exercise on autonomic regulation will be dealt with. Some unique conditions, all akin to space flight environment, such as isolation and confinement, as well as real or simulated microgravity will be discussed, and possible countermeasures considered. Finally, the fundamental difference between indices of tonic and oscillatory components of autonomic mechanisms will be summarized and discussed. Conclusions: Autonomic flexibility is a fundamental property which underscores the capacity of animals and humans to endure acute and chronic exercise. Disregarding, for simplicity, the crucial importance of the type of exercise in determining the adaptive autonomic response, it appears that time and frequency domain techniques might prove convenient to assess, indirectly, autonomic mechanisms from cardiovascular variabilities both at rest and during light and moderate exercise. Beyond molecular aspects, and given the dramatic clinical improvement in prognosis derived from exercise training in diffuse clinical conditions, such as diabetes, obesity, hypertension and coronary artery disease we propose that a combination of epistemologies, such as that provided by exercise physiology and internal medicine might lead to unprecedented opportunities for prevention and well being, based on sound mechanistic knowledge.